An Evaluation To Improve Civilian And Military Relationship In A Conflict Situation: Boko Haram Insurgency In Borno State, Nigeria. - Abalaka, J.N; Ajiteru,S.A.R; Sulaiman T.H (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
This analysis aims to draw attention to the necessity of improving military-civilian interactions in order to promote peace in Borno State. The information used in the paper was taken from literary works of literature. The results demonstrate the critical necessity for good ties between the military and people in order to establish mutually beneficial partnerships that could result in peace during this period of insurgency in Borno State, Nigeria. The primary focus of modern civil-military relations is how civilian leadership manages the armed forces in democracies. Therefore, the elements that influenced the connection between Nigeria's military institution and civilian leadership (2012–2021) were evaluated in this study. The study made the assumption that, since the establishment of the elected civilian government in May 1999, Nigeria's civil-military relations have been significantly shaped by the nature of the interactions between the military and civilian leaderships, the function of civil society, and the external environment. Among the factors found are the knowledge of civilian leadership, the military's readiness to follow orders from civilian leadership, the legal and policy frameworks that governed these leaderships, the functions of international actors, particularly advanced democracies, and civil society. The following results were obtained by using the qualitative content analysis method for data collection and evaluation: The Nigerian military was easier to control thanks to the civilian leadership's understanding of military issues; civil society's role as an advocate for liberal, democratic civil-military relations was very limited; the military's willingness to submit to established authority determined civilian control ability and the role of the international community in terms of its expectations and assistance in the region reform of the security sector fueled the potential for civilian command of the armed forces.